If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -4 = -3x + 11 Reorder the terms: -4 + -4x = -3x + 11 Reorder the terms: -4 + -4x = 11 + -3x Solving -4 + -4x = 11 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -4 + -4x + 3x = 11 + -3x + 3x Combine like terms: -4x + 3x = -1x -4 + -1x = 11 + -3x + 3x Combine like terms: -3x + 3x = 0 -4 + -1x = 11 + 0 -4 + -1x = 11 Add '4' to each side of the equation. -4 + 4 + -1x = 11 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 11 + 4 -1x = 11 + 4 Combine like terms: 11 + 4 = 15 -1x = 15 Divide each side by '-1'. x = -15 Simplifying x = -15
| 73=5y-17 | | -3y+2y-6x+2y-x= | | x+y+xy=11 | | 5x+23=7x+33 | | -3y+2y-6x+2y= | | (4m-120)=2m | | 4x^3-4x+14=0 | | x^2+4x+4=144 | | Ax-3=2 | | 5/6x-4=3/2x+2 | | 3x+4y+x+2y= | | -3x-11=13-5x | | 8x-10=110 | | 1/2x+5=3/4x+1 | | 15+0.25+20+0.05=x | | (4m-120)=5n | | 5t^2-3t-80=0 | | 15x^2+15x+8=0 | | 5(4q-q)-(3p-2q)= | | -7+5x=x+17 | | (m-3)=21 | | 5(4y+2)-14= | | 47+93=5x | | 8+3x-6=3(2-4x)+4(4x-2) | | -7r+1=43 | | x^3-9x+6=0 | | 6x+27=8x-2 | | 9t-4t=70 | | x+411=47.5 | | 4x+3=6x+20 | | 10x^2=19-3x | | 2(2x-10)=3x+15 |